Wheat Cost-Return Budget in Southeast Kansas - Fausett, Marvin R. (My University, 1997)
This publication outlines the expected costs and returns for wheat in southeast Kansas.
MF992_1997_10
Keywords: MF992; Economics; Crops; MF